Who Benefits from Higher Education in Low- and Middle-Income Countries? - Shafiq, M. Najeeb; Toutkoushian, Robert K.; Valerio, Alexandria (Taylor and Francis, 2019)
In this article, we investigate how higher education contributes to the employment and earnings of individuals in labor markets, and whether social origins play a role in the financial benefits from higher education. We focus on these questions in nine low- and middle-income countries: Armenia, Bolivia, Colombia, Georgia, Ghana, Kenya, Laos, Macedonia, and Vietnam. We use the recent Skills Towards Employability and Productivity (STEP) surveys of urban labor force participants to examine individuals’ educational attainment, labor market participation, and earnings. Using logistic regressions, we find that individuals from disadvantaged origins are less likely to obtain a higher education degree. We find that in most of these countries, individuals who have earned a higher education degree are significantly more likely to be in the labor force and find employment, and enjoy sizable earnings premia. The findings are fairly robust with regard to the samples of individuals examined, and the methods used to measure earnings premia. Finally, we find little evidence that the earnings premia from higher education vary by social origins or the likelihood of an individual completing a degree. These results suggest that the benefits from higher education are comparable for individuals from disadvantaged and advantaged social origins.